Startup and MSME’s Development: Identification Based on Business Characteristics of The Millenial Generation in Padang City - Andriani, Chichi; Thaib, Ilham (Future Science, 2021)
This study aims to identify and explain the characteristics of the start-up business of the millennial generation in the city of Padang as a process for startup and MSMEs development. The population in this study is a pioneering business for the millennial generation, namely all coffee shops in Padang city. The sampling technique used purposive sampling technique with the criteria; the coffee shop owners is a millennial generation with birth years 1995-2010, the age of the company ranges from 1-5 years, has more than 2 employees and has a profit above IDR.10,000,000/year. The number of samples in this study using the opinion of Hairs et all so that the samples used were 180 coffee shops. Research data were collected through questionnaires and data analysis using descriptive statistical analysis techniques. From the research results obtained characteristics of; gender, age, educational background, marital status, length of business establishment, number of employees, a form of business ownership, availability of wifi/internet facilities for visitors, membership status on online shopping applications, total sales per year, business ownership status, business legal entity status, separation of company finances from personal finances, business development plans, profit adequacy business and allowance for operating results. Of the 16 characteristics, it is hoped that they will be able to assist in the start-up process and MSMEs development for the millennial generation in Padang city.